Heavy Metal Contain Pb, Hg, Cd and Cu in Whiting Fish (Sillago sihama) Muscle in Estuary of Donan River, Cilacap, Central Java - Nica Cah yani; Djamar T. F Lumban Batu; Sulistiono Sulistiono (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractWaste produced by industrial activities in Donan River can be a heavy metal which is one source of harmful pollutant to the aquatic environment. This study was conducted monthly from August 2015 to January 2016 at the waters of the Donan River estuary. The aims of this study were to analyze the content of heavy metals Pb, Hg, Cd and Cu in whiting fish muscle and determine the tolerance limit to consume fish containing the heavy metals. Commonly, the average content of heavy metal in the whiting fish muscle based on Atomic Absorption Spectrophotometry (AAS) reading exeded the standard limit determined, but there are also some fish whose heavy metal still below the standard limit. The values of heavy metal in the fish muscle range <0,005-9,19 ppm (Pb); 304,50-4535,22 ppb (Hg); 0,11-0,56 ppm (Cd); and 0,36-1,39 ppm (Cu). The maximum weight limit of fish muscle for adults (50 kg) and children (15 kg) are 17,64 g muscle per week and 5,29 g muscle per week, respectively.